The influence of physical agility factors on the achievements of under eighteen soccer team in Sabah - Awang Jasrie Awang Matusin (Faculty of Education and Sports Studies, Universiti Malaysia Sabah, 2024)
The study was conducted with the aim of identifying the influence of physical fitness factors based on the level of achievement among the soccer team for the under 18 years category. The form of this study is an expost facto that was carried out on 216 soccer players aged between 16 years and 17 years in the state of Sabah, who took part in the Majlis Sukan Sekolah Sabah (MSSS) Sepak Ball competition. A total of 24 MSSSD soccer teams participated in this carnival-style match. The team's achievements were categorized into three namely the team qualified to the semifinals, the team qualified to the quarterfinals and the team that only played in the early rounds. A total of eight physical fitness test variables were tested and measured, namely speed, agility, maximum oxygen uptake rate (VO₂Max), endurance and muscle strength of the hands and shoulders, leg power, flexibility, endurance and strength of the abdominal muscles and average out put anaerobic power. The study data were analyzed using the SPSS program inferentially, namely ANOVA Sehala and regreasi pelbagai. The results of the study found that there were significant differences for all factors of physical fitness variables to the category of team achievement. Data analysis results showed that significantly all predictor variables were predictive factors to team performance by contributing as much as 28.7 percent R 2 value of .287 (r = .53) in team performance [F (3,210) = 8.192, P < .05]. All predictor variables were variables that significantly differentiated team achievement categories. The results of the discriminant function analysis using the step wise method found that the two variables that most significantly discriminated the team achievement categories were leg power and shoulder and hand muscle strength. Based on the findings of this study, it is very necessary to the formation of physical fitness principles that correspond to the needs of each team in the game of soccer. The coach must give emphasis in shaping the training program to produce a quality and stable soccer team at the school level up to a higher level. The aspects of speed and agility are important elements in ensuring the success of a soccer team at the youth level.